The Concept Of Islamic Advertising From The Perspective Of Muslim Practitioners - Ani, Noorazlin (2024)
Islamic advertising, as a form of communication, aims to inform and persuade consumers while adhering to Islamic norms. However, in many Muslim countries, advertising practices often follow western paradigms that have created numerous unethical issues inconsistent with Islamic principles. The research consists of two phases namely a theoretical phase addressing the first objective and the empirical phase addressing the second and third objectives. This study explores the concept of Islamic advertising from the perspective of Muslim practitioners. It has three primary objectives: firstly, to identify the concept; secondly, to analyze its framework; and thirdly, to draw conclusions based on the viewpoints of practitioners.